2008
DOI: 10.1016/j.cell.2008.08.038
|View full text |Cite
|
Sign up to set email alerts
|

Fibrils Connect Microtubule Tips with Kinetochores: A Mechanism to Couple Tubulin Dynamics to Chromosome Motion

Abstract: Summary Kinetochores of mitotic chromosomes are coupled to spindle microtubules in ways that allow the energy from tubulin dynamics to drive chromosome motion. Most kinetochore-associated microtubule ends display curving “protofilaments,” strands of tubulin dimers that bend away from the microtubule axis. Both a kinetochore “plate” and an encircling, ring-shaped protein complex have been proposed to link protofilament bending to poleward chromosome motion. Here we show by electron tomography that slender fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
240
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(253 citation statements)
references
References 46 publications
(65 reference statements)
13
240
0
Order By: Relevance
“…This model is consistent with super-resolution imaging that shows CENP-H localizing within CENP-A rich subdomains and excluded from H3-domains. The model is also consistent with electron-microscopy data, which shows that the microtubule-tip is very precisely centered above the centromeric nucleosome(s) [58,59]. The limited conservation of the CCAN in budding yeast and worms may simply reflect the presence of a single attachment site or distributed attachment sites across the chromosome respectively.…”
Section: Future Viewsupporting
confidence: 75%
“…This model is consistent with super-resolution imaging that shows CENP-H localizing within CENP-A rich subdomains and excluded from H3-domains. The model is also consistent with electron-microscopy data, which shows that the microtubule-tip is very precisely centered above the centromeric nucleosome(s) [58,59]. The limited conservation of the CCAN in budding yeast and worms may simply reflect the presence of a single attachment site or distributed attachment sites across the chromosome respectively.…”
Section: Future Viewsupporting
confidence: 75%
“…It can also maintain load-bearing attachments to dynamic microtubules (Franck et al 2007;Grishchuk et al 2008a;Volkov et al 2013), and quantitative fluorescence data indicate that there are sufficient Dam1 complexes at kinetochores in vivo to form rings (Joglekar et al 2006). When Dam1 is tethered to beads in a manner that might mimic fibrils, it can maintain much greater load in vitro (Volkov et al 2013), and fibril-like connections have been observed by tomography on mammalian cells (McIntosh et al 2008). While these data support the conformational wave model, a single Dam1 complex is sufficient to diffuse along a microtubule and to attach to disassembling tips in vitro (Gestaut et al 2008;Grishchuk et al 2008b).…”
Section: Kinetochore-microtubule Attachments and Coupling Activitymentioning
confidence: 97%
“…Depending on the number of binding elements, the lattice rate can be negligibly slow, but the tip rate will remain fast enough to support tip tracking (Hill 1985;Powers et al 2009). The other major mechanism that has been supported by both theoretical considerations and experimental evidence is referred to as the "conformational wave" model (Koshland et al 1988;Molodtsov et al 2005;McIntosh et al 2008). This model and a variation called the "forced walk" theorize that a portion of the kinetochore forms a ring or fibrils that are pushed on by depolymerizing filaments in the microtubule to move the kinetochore.…”
Section: Kinetochore-microtubule Attachments and Coupling Activitymentioning
confidence: 99%
“…What about the structural and molecular nature of the coupler at kinetochores? For the skeptics about rings and collars at kinetochores, McIntosh and colleagues used electron tomography to show that kinetochore fibrils of about 50 nm are connected to curved protofilaments at microtubule plus-ends [148], defining a structural entity at kinetochores that could effectively work as a coupler for chromosome motion by microtubule plus-end depolymerization. By measuring the curvature of bending protofilaments associated with kinetochore fibrils they estimated that each depolymerizing microtubule could produce a force of ~40 pN, in agreement with previous estimations [122].…”
Section: Force Generation By Microtubule Depolymerization From Plus-endsmentioning
confidence: 99%